Homeschoolers and Public Libraries: A Synergistic Relationship - Jennings, Cynthia (Maine Policy Review, 2013)
Homeschoolers are commonly heavy users of their local libraries. this article discusses how libraries can become educational “hubs” for for homeschoolers by developing programs and services to support this burgeoning population.